Delay in diagnosis and treatment of cancer in Peru. Study of 1,000 cases - Cáceres, Eduardo (2015)
Thousand consecutive cases of histologically proven cancer, seen at the National Institute of Neoplastic Diseases in the period of one year, have been studied and the responsibility for the patient and the physician in delayed diagnosis and treatment has been established. The main cause of delay in diagnosis has led to cause the patient's responsibility, 60.9 percent. Ignorance on the part of the patient has been the main cause in the delay, 94 .7 percent. The delay by the doctor, 25 .7 percent is attributed mainly to the fact that the cancer was not suspected and consequently appropriate studies are not checked for a diagnosis. Negligence, wrong inadequate examinations and recommendations were the main reasons for the delay. An individual who had symptoms for three or more months before consulting the doctor or consulted a doctor before this punishment in time and could not have a proper diagnosis or treatment, has wasted valuable time. In our series of 745 patients that is 74.5 percent suffered from this delay. The physician's responsibility to make an early diagnosis is limited to inaccessible cancers where the diagnosis requires special tests, but also accessible cancers, probably because the doctor did not suspect or does not interpret the signs and symptoms of early cancer not only. For this study it is obvious the urgent need for improved early diagnosis of cancer through patient education through adequate public propaganda and dissemination of knowledge of cancer among physicians. This work should be carried out by medical schools, medical societies and institutions interested in the problem of cancer.